A Case Study of Malaysian Pedestrian Walking Speed at Shopping Malls in Kuala Lumpur, Malaysia using Human Behaviour Simulator (HBS) - Mohamad Ali, Mohd Firdaus; Abustan, Muhammad Salleh; Abu Talib, Siti Hidayah (International Journal of Integrated Engineering, 2019)
Rate of pedestrian walking speeds are influenced by some factors such as gender, age and location. Numerous research had been conducted to deepen the understanding of pedestrian walking speed because it is one of the keys in understanding the pedestrian walking behaviour. This case of study was conducted at two shopping malls in Kuala Lumpur namely MyTown Shopping Centre and Sunway Velocity Mall, with two main objectives which are i) To determine the average walking speed of pedestrian by considering the factors of age and gender; and ii) To compare the average walking speed that considered age as the factor of comparison between the pedestrian walking speed at shopping malls and crosswalk. Demographic factors of pedestrian walking speed in this study are on the basis of gender (male and female) and 7 groups of age categories consist of children, adult men and women, senior adult men and women, over 70 and disabled person. A camcorder was used to obtain the data of experiment by making video recording of the movement of people that were walking and roaming around at the main atriums of the shopping malls for 30 minutes. Hence, data analysis was completed by using a software named Human Behaviour Simulator (HBS) for analysing the data that were extracted from the video. The result of this study was male pedestrian walked faster than female with the average walking speed of 0.93m/s and 0.81m/s respectively. Also, people in shopping malls walked slower compared to pedestrian who were walking at crosswalk.